Binder composition for all-solid secondary battery, slurry composition for all-solid secondary battery, solid electrolyte layer and all-solid secondary battery
By using a binder composition containing an acrylic polymer and a coagulant, a solid-containing electrolyte layer with excellent high-temperature storage characteristics is formed, and the problem of reducing capacity of all-solid secondary batteries under high temperature conditions is solved, and the effect of significantly improving the high-temperature storage characteristics is achieved.
Patent Information
- Application Number
- CN201980060817.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2018-09-28
- Filing Date
- 2019-09-20
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2039-09-20
AI Technical Summary
All-solid secondary batteries have a problem of capacity reduction under high temperature conditions, and they need to improve their high-temperature storage characteristics.
Using a binder composition containing an acrylic polymer and a prescribed amount of a coagulant, a solid-containing electrolyte layer capable of forming excellent high-temperature storage characteristics was prepared.
The solid-containing electrolyte layer formed using the binder composition is significantly improved in the high-temperature storage characteristics of the all-solid secondary battery.
Smart Images

Figure BDA0002980074210000281 
Figure BDA0002980074210000291
Abstract
Description
Technical Field
[0001] The present invention relates to a binder composition for an all-solid battery, a slurry composition for an all-solid battery, a solid electrolyte layer and an all-solid secondary battery. Background Art
[0002] In recent years, the demand for lithium-ion secondary batteries and other secondary batteries has been increasing in various applications, including mobile terminals such as mobile information terminals and mobile electronic devices, as well as small household power storage devices, motorcycles, electric vehicles, hybrid electric vehicles, etc. Moreover, with the widening of applications, the safety of secondary batteries is required to be further improved.
[0003] Therefore, all-solid-state batteries that use solid electrolytes instead of organic solvent electrolytes that are highly flammable and have a high risk of ignition when leaked have attracted attention as safe secondary batteries.
[0004] Here, the all-solid secondary battery has a positive electrode, a negative electrode and a solid electrolyte layer between the positive electrode and the negative electrode. Moreover, the electrodes (positive electrode, negative electrode) of the all-solid secondary battery are formed by, for example, the following methods: a slurry composition comprising an electrode active material (positive electrode active material, negative electrode active material), a binder and a solid electrolyte is applied to the current collector, and the applied slurry composition is dried and an electrode composite material layer (positive electrode composite material layer, negative electrode composite material layer) is arranged on the current collector. In addition, the solid electrolyte layer of the all-solid secondary battery is formed by, for example, the following methods: a slurry composition comprising a binder and a solid electrolyte is applied to an electrode or a demoulding substrate, and the applied slurry composition is dried.
[0005] In addition, acrylic polymers have been used as binders for forming solid electrolyte layers. For example, in Patent Document 1, a monomer is emulsion polymerized in water in the presence of sodium dodecylbenzenesulfonate as an emulsifier to obtain an aqueous dispersion of an acrylic polymer, and solvent replacement is performed in an organic solvent to prepare a binder composition containing an acrylic polymer and an organic solvent.
[0006] Prior art literature
[0007] Patent Literature
[0008] Patent document 1: International Publication No. 2016 / 152262. Summary of the invention
[0009] Problem that the invention aims to solve
[0010] Here, in recent years, in fields such as electric vehicles, all-solid secondary batteries are often exposed to high temperature conditions (e.g., above 80°C), and there is a problem of suppressing the reduction of capacity under high temperature conditions (i.e., improving high temperature storage characteristics). That is, it is required to use a binder composition containing an acrylic polymer to form a solid electrolyte layer, an electrode composite material layer, and other layers containing a solid electrolyte (hereinafter referred to as "solid electrolyte-containing layer") to fully ensure the high temperature storage characteristics of the all-solid secondary battery.
[0011] Therefore, an object of the present invention is to provide a binder composition for an all-solid secondary battery and a slurry composition for an all-solid secondary battery that can form a solid electrolyte-containing layer that enables an all-solid secondary battery to exhibit excellent high-temperature storage characteristics.
[0012] Another object of the present invention is to provide a solid electrolyte layer that enables an all-solid secondary battery to exhibit excellent high-temperature storage characteristics and an all-solid secondary battery having excellent high-temperature storage characteristics.
[0013] Solutions for solving problems
[0014] The present inventors have conducted in-depth research to solve the above problems. Then, the present inventors newly discovered that a slurry composition prepared using a binder composition containing an acrylic polymer and a predetermined amount of a coagulant can form a solid electrolyte layer that enables an all-solid secondary battery to exhibit excellent high-temperature storage characteristics, thereby completing the present invention.
[0015] That is, the present invention aims to solve the above-mentioned problems advantageously, and the binder composition for all-solid secondary batteries of the present invention is characterized in that it comprises an acrylic acid polymer and a coagulant of 500 mass ppm or more and 5000 mass ppm or less relative to the above-mentioned acrylic acid polymer. If a slurry composition comprising such a binder composition is used to form a solid electrolyte layer, the binder composition comprises an acrylic acid polymer and a coagulant, and the amount of the coagulant relative to the acrylic acid polymer is a ratio within the above range, then the all-solid secondary battery can exert excellent high temperature storage characteristics.
[0016] In the present invention, the "acrylic polymer" means a polymer containing a (meth)acrylic acid ester monomer unit in a ratio of 50% by mass or more.
[0017] Here, in the present invention, "(meth)acrylic acid" means acrylic acid and / or methacrylic acid.
[0018] In the present invention, “containing a monomer unit” means “a repeating unit derived from the monomer is contained in a polymer obtained by using the monomer”.
[0019] In the present invention, the ratio of each repeating unit (monomer unit) constituting the polymer can be expressed as follows: 1 H-NMR and 13 C-NMR or other nuclear magnetic resonance (NMR) method.
[0020] In the present invention, the "coagulant" is a substance added to aggregate and coagulate the acrylic polymer dispersed in water, and is a substance that instantly and irreversibly coagulates the acrylic polymer particles dispersed in water at room temperature (eg, 15°C to 30°C).
[0021] In the present invention, the content of the "coagulant" relative to the "acrylic polymer" can be determined by elemental analysis.
[0022] Here, in the binder composition for all-solid secondary batteries of the present invention, the coagulant is preferably a metal sulfate having a valency of more than 1 and less than 3. If a metal sulfate having a valency of more than 1 and less than 3 is used as a coagulant, the manufacturing efficiency of the binder composition can be ensured and the high-temperature storage characteristics of the all-solid secondary battery can be fully improved.
[0023] In addition, the binder composition for an all-solid secondary battery of the present invention can use an emulsion polymer as the acrylic polymer.
[0024] Furthermore, the binder composition for an all-solid secondary battery of the present invention may further contain an organic solvent.
[0025] In addition, the present invention is aimed at advantageously solving the above-mentioned problems, and the slurry composition for all-solid secondary batteries of the present invention is characterized in that it comprises a solid electrolyte and a binder composition for all-solid secondary batteries containing the above-mentioned organic solvent. If such a slurry composition comprising a solid electrolyte and a binder composition containing an organic solvent is used to form a solid electrolyte layer, the all-solid secondary battery can exert excellent high-temperature storage characteristics.
[0026] Here, the slurry composition for all-solid secondary batteries of the present invention can contain an inorganic solid electrolyte as the solid electrolyte.
[0027] The slurry composition for all-solid secondary batteries of the present invention may further contain an electrode active material. When the slurry composition for all-solid secondary batteries containing an electrode active material is used, an electrode composite material layer that enables the all-solid secondary battery to exhibit excellent high-temperature storage characteristics can be well formed.
[0028] In addition, the present invention aims to advantageously solve the above-mentioned problems, and the solid electrolyte layer of the present invention is characterized in that it is formed using any of the above-mentioned slurry compositions for all-solid secondary batteries. The solid electrolyte layer formed using the above-mentioned slurry composition for all-solid secondary batteries can enable the all-solid secondary battery to exert excellent high-temperature storage characteristics.
[0029] Furthermore, the present invention aims to solve the above-mentioned problems advantageously, and the all-solid secondary battery of the present invention is characterized in that it has the above-mentioned solid electrolyte layer. If the above-mentioned solid electrolyte layer is used, an all-solid secondary battery that can exert excellent high-temperature storage characteristics can be obtained.
[0030] Effects of the Invention
[0031] According to the present invention, it is possible to provide a binder composition for an all-solid secondary battery and a slurry composition for an all-solid secondary battery that can form a solid electrolyte-containing layer that enables an all-solid secondary battery to exhibit excellent high-temperature storage characteristics.
[0032] Furthermore, according to the present invention, it is possible to provide a solid electrolyte layer containing an all-solid secondary battery that enables the all-solid secondary battery to exhibit excellent high-temperature storage characteristics and an all-solid secondary battery having excellent high-temperature storage characteristics. DETAILED DESCRIPTION
[0033] Hereinafter, embodiments of the present invention will be described in detail.
[0034] Here, the binder composition for all-solid secondary batteries of the present invention can be used when preparing the slurry composition for all-solid secondary batteries of the present invention. Moreover, the slurry composition for all-solid secondary batteries of the present invention can be used when forming an electrode composite material layer, a solid electrolyte layer, etc. containing solid electrolyte layers that can be used for all-solid secondary batteries such as all-solid lithium ion secondary batteries. In addition, in the all-solid secondary battery of the present invention, at least one layer selected from the positive electrode composite material layer of the positive electrode, the negative electrode composite material layer of the negative electrode, and the solid electrolyte layer is formed by the solid electrolyte layer of the present invention formed using the slurry composition for all-solid secondary batteries of the present invention.
[0035] (Binder composition for all-solid secondary batteries)
[0036] The adhesive composition of the present invention comprises an acrylic polymer and a coagulant, and may optionally contain other components such as an organic solvent. The adhesive composition of the present invention needs to contain the coagulant in an amount of 500 ppm by mass or more and 5000 ppm by mass or less relative to the acrylic polymer.
[0037] Furthermore, according to the slurry composition prepared using the binder composition of the present invention, a solid electrolyte-containing layer can be formed that enables an all-solid secondary battery to exhibit excellent high-temperature storage characteristics.
[0038] <Acrylic polymer>
[0039] The acrylic polymer is a component that performs a binder function in the solid electrolyte-containing layer formed from the slurry composition containing the binder composition. The binder composition of the present invention may contain one acrylic polymer or two or more acrylic polymers.
[0040] <<Composition>>
[0041] Here, as described above, the acrylic polymer is a polymer containing 50% by mass or more of a (meth)acrylic acid ester monomer unit as a repeating unit. In addition, the acrylic polymer may contain repeating units other than the (meth)acrylic acid ester monomer unit (hereinafter referred to as "other repeating units").
[0042] [(Meth)acrylate monomer unit]
[0043] The (meth)acrylate monomer that can form the (meth)acrylate monomer unit is not particularly limited, and examples thereof include (meth)acrylate alkyl ester monomers and (meth)acrylate alkoxyalkyl ester monomers. The (meth)acrylate monomers can be used alone or in combination of two or more.
[0044] As the (meth) acrylate alkyl ester monomer, there is no particular limitation, preferably the ester of an alkyl alcohol having a carbon number of more than 1 and less than 8 and (meth) acrylic acid. Specifically, methyl (meth) acrylate, ethyl (meth) acrylate, n-propyl (meth) acrylate, isopropyl (meth) acrylate, n-butyl (meth) acrylate, isobutyl (meth) acrylate, n-hexyl (meth) acrylate, 2-ethylhexyl (meth) acrylate and cyclohexyl (meth) acrylate, etc. can be cited. These can be used alone or in combination of two or more. Moreover, among these, from the viewpoint of fully improving the high temperature storage characteristics of the all-solid secondary battery, ethyl (meth) acrylate and n-butyl (meth) acrylate are preferred, and ethyl acrylate and n-butyl acrylate are more preferred.
[0045] As (meth) acrylate alkoxyalkyl ester monomer, it is not particularly limited, preferably the ester of alkoxyalkyl alcohol and (meth) acrylic acid with a carbon number of more than 2 and less than 8. Specifically, methoxymethyl (meth) acrylate, ethoxymethyl (meth) acrylate, 2-methoxyethyl (meth) acrylate, 2-ethoxyethyl (meth) acrylate, 2-propoxyethyl (meth) acrylate, 2-butoxyethyl (meth) acrylate, 3-methoxypropyl (meth) acrylate and 4-methoxybutyl (meth) acrylate, etc. can be cited. These can be used alone or in combination of two or more. And, among these, from the viewpoint of fully improving the high temperature storage characteristics of all-solid secondary batteries, preferably 2-ethoxyethyl (meth) acrylate and 2-methoxyethyl (meth) acrylate, particularly preferably 2-ethoxyethyl acrylate and 2-methoxyethyl acrylate.
[0046] In addition, from the viewpoint of ensuring the adhesiveness of the acrylic polymer, the content of the (meth) acrylic acid ester monomer unit in the acrylic polymer needs to be 50% by mass or more, preferably 60% by mass or more, and more preferably 70% by mass or more. On the other hand, the upper limit of the content of the (meth) acrylic acid ester monomer unit in the acrylic polymer is not particularly limited and can be 100% by mass or less.
[0047] In addition, from the viewpoint of sufficiently improving the high-temperature storage characteristics of the all-solid secondary battery, the acrylic polymer preferably contains 30% by mass or more and 100% by mass or less of an alkyl (meth)acrylate monomer unit as a (meth)acrylate monomer unit.
[0048] Furthermore, from the viewpoint of sufficiently improving the high-temperature storage characteristics of the all-solid secondary battery, the acrylic polymer preferably contains both ethyl acrylate units and n-butyl acrylate units.
[0049] [Other repeating units]
[0050] As other repeating units, there are no particular limitations as long as they are repeating units derived from monomers copolymerizable with the above-mentioned (meth)acrylate monomers, and examples thereof include aromatic vinyl monomer units, α,β-ethylenically unsaturated nitrile monomer units, acrylamide monomer units, etc. In addition, monomers that can form other repeating units can be used alone or in combination of two or more.
[0051] Examples of the aromatic vinyl monomer that can form the aromatic vinyl monomer unit include styrene, α-methylstyrene, and divinylbenzene, of which one species may be used alone or two or more species may be used in combination.
[0052] Examples of the α,β-ethylenically unsaturated nitrile monomer that can form the α,β-ethylenically unsaturated nitrile monomer unit include acrylonitrile and methacrylonitrile. These can be used alone or in combination of two or more.
[0053] Examples of the acrylamide monomers that can form the acrylamide monomer units include acrylamide and methacrylamide, etc. These can be used alone or in combination of two or more.
[0054] In addition to the above-mentioned aromatic vinyl monomers, α,β-ethylenically unsaturated nitrile monomers, and acrylamide monomers, olefin monomers such as ethylene, vinyl acetate, propylene, butadiene, and isoprene may be used to form other repeating units.
[0055] Among these, as the monomer that can form other repeating units, styrene, acrylonitrile, methacrylonitrile, ethylene, and vinyl acetate are preferred, and acrylonitrile, methacrylonitrile, and ethylene are more preferred.
[0056] The content ratio of other repeating units in the acrylic polymer is preferably 50% by mass or less, more preferably 40% by mass or less, and further preferably 30% by mass or less.
[0057] <<Preparation method>>
[0058] The method for preparing the acrylic polymer by polymerizing the above-mentioned monomers is not particularly limited, but the acrylic polymer is preferably prepared by emulsion polymerization as described in the section "Method for producing adhesive composition." That is, the acrylic polymer is preferably a polymer prepared by emulsion polymerization (emulsion polymer).
[0059] <Coagulant>
[0060] As mentioned above, the coagulant is a substance that can cause the acrylic polymer dispersed in water to condense and solidify. Here, in the present invention, there is no particular limitation, and the coagulant is usually added to solidify the acrylic polymer in the aqueous dispersion (e.g., emulsion) obtained by polymerization reaction in water, and remains in the adhesive composition.
[0061] <<Type>>
[0062] Here, the coagulant is not particularly limited, and examples thereof include metal salts having a valency of more than 1 and a valency of less than 3. Here, the metal salt having a valency of more than 1 and a valency of less than 3 is a salt containing a metal that becomes a metal ion having a valency of more than 1 and a valency of less than 3 when dissolved in water, and is not particularly limited, and examples thereof include salts of inorganic acids such as hydrochloric acid, nitric acid, and sulfuric acid, organic acids such as acetic acid, and metals selected from sodium, potassium, lithium, magnesium, calcium, zinc, titanium, manganese, iron, cobalt, nickel, aluminum, and tin. In addition, hydroxides of these metals can also be used.
[0063] As specific examples of metal salts with a valence of more than 1 and less than 3, metal chlorides such as sodium chloride, potassium chloride, lithium chloride, magnesium chloride, calcium chloride, zinc chloride, titanium chloride, manganese chloride, iron chloride, cobalt chloride, nickel chloride, aluminum chloride, and tin chloride can be cited; metal nitrates such as sodium nitrate, potassium nitrate, lithium nitrate, magnesium nitrate, calcium nitrate, zinc nitrate, titanium nitrate, manganese nitrate, iron nitrate, cobalt nitrate, nickel nitrate, aluminum nitrate, and tin nitrate; metal sulfates such as sodium sulfate, potassium sulfate, lithium sulfate, magnesium sulfate, calcium sulfate, zinc sulfate, titanium sulfate, manganese sulfate, iron sulfate, cobalt sulfate, nickel sulfate, aluminum sulfate, and tin sulfate. Among these, calcium chloride, sodium chloride, magnesium chloride, zinc chloride, and metal sulfate are preferred from the viewpoint of ensuring the manufacturing efficiency of the binder composition and fully improving the high temperature storage characteristics of the all-solid secondary battery, and metal sulfates are more preferred, and sodium sulfate and magnesium sulfate are further preferred. In addition, these can be used alone or in combination.
[0064] <<Content>>
[0065] The content of the coagulant contained in the adhesive composition of the present invention needs to be 500 mass ppm or more and 5000 mass ppm or less, preferably 800 mass ppm or more, preferably 4500 mass ppm or less, more preferably 4000 mass ppm or less, and further preferably 3500 mass ppm or less, relative to the acrylic polymer.
[0066] Here, as mentioned above, coagulant is usually used to solidify the acrylic polymer in the aqueous dispersion obtained by the polymerization reaction in water and add, in such a case, coagulant can inevitably remain in the binder composition (particularly acrylic polymer) obtained. The inventor finds that when the amount of the coagulant is too much, the high temperature storage characteristics of the all-solid secondary battery can not be fully guaranteed. That is, when the content of the coagulant included in the binder composition exceeds 5000 mass ppm relative to the acrylic polymer, the all-solid secondary battery can not be made to play an excellent high temperature storage characteristic. On the other hand, when the amount of the coagulant used to solidify the acrylic polymer in the aqueous dispersion is reduced or the acrylic polymer after the solidification is excessively cleaned in order to reduce the amount of the coagulant, the recovery rate of the acrylic polymer will be too low, the manufacturing process becomes complicated, etc., and the manufacturing efficiency of the binder composition will be impaired. From this viewpoint, the content of the coagulant included in the binder composition needs to be more than 500 mass ppm.
[0067] The content (residual amount) of the coagulant in the adhesive composition can be adjusted by changing the type of emulsifier used to prepare the acrylic polymer, the amount of the coagulant added to the aqueous dispersion of the acrylic polymer, and the washing conditions of the acrylic polymer (adhesive composition) after coagulation.
[0068] <<Other ingredients>>
[0069] There are no particular limitations on components that may be optionally contained in the adhesive composition in addition to the acrylic polymer and coagulant described above.
[0070] For example, the adhesive composition can contain an organic solvent as another component. Here, examples of the organic solvent include: chain aliphatic hydrocarbons such as hexane; cyclic aliphatic hydrocarbons such as cyclopentane and cyclohexane; aromatic hydrocarbons such as toluene and xylene; ketones such as ethyl methyl ketone, cyclohexanone, and diisobutyl ketone; esters such as ethyl acetate, butyl acetate, butyl butyrate, γ-butyrolactone, and ε-caprolactone; nitriles such as acetonitrile and propionitrile; ethers such as tetrahydrofuran, ethylene glycol diethyl ether, and n-butyl ether; alcohols such as methanol, ethanol, isopropanol, ethylene glycol, and ethylene glycol monomethyl ether; amides such as N-methylpyrrolidone and N,N-dimethylformamide, etc.
[0071] Among them, from the viewpoint of suppressing the degradation of the solid electrolyte and obtaining a solid electrolyte layer with excellent ion conductivity, a non-polar organic solvent is preferably used as the organic solvent, and hexane or xylene is more preferably used. Furthermore, from the viewpoint of further improving the high-temperature storage characteristics of the all-solid secondary battery, xylene is particularly preferred.
[0072] The above-mentioned organic solvents can be used alone or in combination of two or more.
[0073] In addition, in the binder composition, as other components, the components for preparing the acrylic polymer described in the "Method for producing the binder composition" may remain, and any components described in the "Slurry composition for all-solid secondary batteries" may be added.
[0074] <Method for producing adhesive composition>
[0075] The method for producing the adhesive composition of the present invention is not particularly limited, but is preferably produced through the following steps, for example:
[0076] A step of emulsion-polymerizing a monomer containing a (meth)acrylate monomer in the presence of an emulsifier to obtain an emulsion polymerization solution containing an acrylic polymer (emulsion polymerization step),
[0077] a step of adding a coagulant to the emulsion polymerization liquid to coagulate the acrylic polymer to obtain water-containing granules (coagulation step);
[0078] a step of washing the water-containing pellets (washing step), and
[0079] A step of drying the washed water-containing granules (drying step).
[0080] In addition, the method for producing the adhesive composition through the above-mentioned emulsion polymerization step, coagulation step, washing step and drying step may also have steps other than the emulsion polymerization step, coagulation step, washing step and drying step (hereinafter referred to as "other steps").
[0081] <<Emulsion polymerization process>>
[0082] In the emulsion polymerization step, the monomers such as the (meth)acrylate monomers are emulsion polymerized in water in the presence of an emulsifier to obtain an emulsion polymerization solution containing an acrylic polymer (aqueous dispersion of acrylic polymer). Here, the emulsion polymerization method in the emulsion polymerization step is not particularly limited as long as it can polymerize monomers such as the (meth)acrylate monomers, and any method using, for example, an emulsifier, a polymerization initiator, a polymerization terminator, etc. can be used.
[0083] The emulsifier is not particularly limited, and any of a nonionic emulsifier, an anionic emulsifier, and a cationic emulsifier can be used.
[0084] Examples of the nonionic emulsifier include polyoxyethylene alkyl ethers such as polyoxyethylene lauryl ether, polyoxyethylene alkylphenol ethers such as polyoxyethylene nonylphenyl ether, polyoxyethylene alkyl esters, polyoxyethylene sorbitan alkyl esters, polyoxyethylene polyoxypropylene glycol, and polyethylene glycol monostearate.
[0085] Examples of the anionic emulsifier include salts of fatty acids such as myristic acid, palmitic acid, oleic acid, and linolenic acid, alkylbenzenesulfonates such as sodium dodecylbenzenesulfonate, higher alcohol sulfates such as sodium lauryl sulfate, higher phosphates such as sodium alkyl phosphates, and alkyl sulfosuccinates.
[0086] Examples of the cationic emulsifier include alkyltrimethylammonium chloride, dialkylammonium chloride, and benzylammonium chloride.
[0087] These emulsifiers can be used alone or in combination of two or more. Moreover, among these emulsifiers, nonionic emulsifiers and anionic emulsifiers are preferred, and nonionic emulsifiers and anionic emulsifiers are more preferably used in combination. By using nonionic emulsifiers and anionic emulsifiers in combination, the generation of stains caused by the attachment of acrylic polymer to the polymerization device (e.g., polymerization tank) used for emulsion polymerization can be effectively suppressed, and the amount of coagulant used in the following coagulation process can be reduced, and as a result, the amount of coagulant in the final binder composition (acrylic polymer) can be reduced.
[0088] Furthermore, by using a nonionic emulsifier and an anionic emulsifier in combination, the emulsification effect can be improved, so the amount of the emulsifier itself can be reduced. As a result, the residual amount of the emulsifier contained in the final adhesive composition (acrylic polymer) can be reduced, thereby further improving the water resistance of the obtained acrylic polymer.
[0089] Here, the amount of the emulsifier used is preferably 0.1 to 5 parts by mass, more preferably 0.5 to 4 parts by mass, and even more preferably 1 to 3 parts by mass, based on the total amount of the emulsifier used, relative to 100 parts by mass of all monomers used for polymerization.
[0090] In addition, when a nonionic emulsifier and an anionic emulsifier are used in combination, the amount of the nonionic emulsifier used is preferably 0.1 to 4 parts by mass, more preferably 0.2 to 3 parts by mass, and further preferably 0.5 to 2 parts by mass, relative to 100 parts by mass of all monomers used for polymerization, and the amount of the anionic emulsifier used is preferably 0.1 to 4 parts by mass, more preferably 0.2 to 3 parts by mass, and further preferably 0.5 to 2 parts by mass. In addition, the use ratio is preferably 1 / 99 to 99 / 1, more preferably 10 / 90 to 80 / 20, and further preferably 25 / 75 to 75 / 25 in terms of the mass ratio of the nonionic emulsifier / anionic emulsifier.
[0091] As the polymerization initiator, it is possible to use: azo compounds such as azobisisobutyronitrile; organic peroxides such as diisopropylbenzene hydroperoxide, cumene hydroperoxide, terpene hydroperoxide, benzoyl peroxide; inorganic peroxides such as potassium persulfate, sodium persulfate, ammonium persulfate, etc. These polymerization initiators can be used alone or in combination of two or more. The amount of the polymerization initiator used is preferably 0.001 parts by mass or more and 1.0 parts by mass or less relative to 100 parts by mass of all monomers used for polymerization.
[0092] In addition, the organic peroxide and inorganic peroxide as polymerization initiators are preferably used in combination with a reducing agent as a redox polymerization initiator. The reducing agent used in combination is not particularly limited, and examples thereof include: compounds containing reduced metal ions such as ferrous sulfate, sodium ferric hexamethylenediaminetetraacetate, and cuprous cyclohexane; ascorbic acid (salts) such as ascorbic acid, sodium ascorbate, and potassium ascorbate; isoascorbic acid (salts) such as isoascorbic acid, sodium isoascorbate, and potassium isoascorbate; sugars; sulfinates such as sodium hydroxymethanesulfinate; sodium sulfite, potassium sulfite, sodium bisulfite, and aldehyde sulfite; Sulfites such as sodium hydrogen sulfate and potassium hydrogen sulfite; pyrosulfites such as sodium pyrosulfite, potassium pyrosulfite, sodium pyrosulfite, potassium pyrosulfite; thiosulfates such as sodium thiosulfate and potassium thiosulfate; phosphorous acids (salts) such as phosphorous acid, sodium phosphite, potassium phosphite, sodium hydrogen phosphite, and potassium hydrogen phosphite; pyrophosphorous acids (salts) such as pyrophosphorous acid, sodium pyrophosphite, potassium pyrophosphite, sodium hydrogen pyrophosphite, and potassium hydrogen pyrophosphite; sodium formaldehyde sulfoxylate, etc. These reducing agents can be used alone or in combination of two or more. The amount of the reducing agent used is preferably 0.0003 parts by mass or more and 0.4 parts by mass or less relative to 100 parts by mass of the polymerization initiator.
[0093] In the present invention, "acid (salt)" means an acid and / or a salt of the acid.
[0094] Examples of the polymerization terminator include hydroxylamine, hydroxylamine sulfate, diethylhydroxylamine, hydroxylamine sulfonic acid and its alkali metal salts, sodium dimethyldithiocarbamate, hydroquinone, etc. The amount of the polymerization terminator used is not particularly limited, but is preferably 0.1 parts by mass or more and 2 parts by mass or less relative to 100 parts by mass of all monomers used for polymerization.
[0095] The amount of water used is not particularly limited, but is preferably 80 parts by mass or more and 500 parts by mass or less, and more preferably 100 parts by mass or more and 300 parts by mass or less, based on 100 parts by mass of all monomers used for polymerization.
[0096] In addition, during the emulsion polymerization, polymerization auxiliary materials such as a molecular weight modifier, a particle size modifier, a chelating agent, and an oxygen scavenger may be used as necessary. As these polymerization auxiliary materials, any known materials may be used.
[0097] Here, the emulsion polymerization can be carried out in any of the following ways: intermittent, semi-intermittent, and continuous, preferably semi-intermittent. Specifically, preferably: from the start of the polymerization reaction to any time, in a reaction system comprising a polymerization initiator and a reducing agent, while continuously dropping the monomer used for polymerization into the polymerization reaction system, while carrying out the polymerization reaction, etc. From the start of the polymerization reaction to any time, while continuously dropping at least one of the monomer used for polymerization, a polymerization initiator, and a reducing agent into the polymerization reaction system, while carrying out the polymerization reaction. Moreover, more preferably: from the start of the polymerization reaction to any time, while continuously dropping all the monomers, polymerization initiators, and reducing agents used for polymerization into the polymerization reaction system, while carrying out the polymerization reaction. By carrying out the polymerization reaction while continuously dropping these, the emulsion polymerization can be carried out stably, thereby enabling the polymerization reaction rate to be improved. In addition, the polymerization is usually carried out at a temperature range of above 0°C and below 70°C, preferably above 5°C and below 50°C.
[0098] In addition, when the polymerization reaction is carried out while continuously dropping the monomer for polymerization, it is preferred that the monomer for polymerization is mixed with an emulsifier and water to prepare a monomer emulsion, and the monomer emulsion is continuously dropped. There is no particular limitation on the method for preparing the monomer emulsion, and examples include a method of stirring the total amount of the monomer for polymerization, the total amount of the emulsifier and water using a homogenizer, a disc turbine stirrer or the like. The amount of water used in the monomer emulsion is preferably 10 parts by mass or more and 70 parts by mass or less, and more preferably 20 parts by mass or more and 50 parts by mass or less, relative to 100 parts by mass of the total monomer for polymerization.
[0099] In addition, when the polymerization reaction is carried out while continuously dropping all the monomers, polymerization initiators and reducing agents used for polymerization into the polymerization reaction system from the start of the polymerization reaction to an arbitrary time, these can be added dropwise to the polymerization system using respective dropping devices, or at least the polymerization initiator and reducing agent can be mixed in advance, made into an aqueous solution as required, and added dropwise to the polymerization system from the same dropping device. After the addition is completed, the reaction can be continued for an arbitrary time in order to further increase the polymerization reaction rate.
[0100] <<Solidification process>>
[0101] In the coagulation step, a coagulant is added to the emulsion polymerization solution obtained in the above-mentioned emulsion polymerization step to coagulate the acrylic polymer, thereby obtaining water-containing pellets (coagulated product containing the acrylic polymer, the coagulant and water).
[0102] As the coagulant, the above-mentioned metal salt having a valency of more than 1 and less than 3 can be preferably used. From the viewpoint of making the content (residual amount) of the coagulant in the acrylic acid polymer finally obtained within the above range, the amount of the coagulant used is preferably more than 1 part by mass and less than 20 parts by mass, and more preferably more than 2 parts by mass and less than 15 parts by mass, relative to 100 parts by mass of the acrylic acid polymer in the emulsion polymerization solution.
[0103] The solidification temperature is not particularly limited, but is preferably 50°C or higher and 90°C or lower, and more preferably 60°C or higher and 80°C or lower.
[0104] <<Cleaning process>>
[0105] In the washing step, the water-containing pellets obtained in the above-mentioned coagulation step are washed. By washing the water-containing pellets, the residual amount of components (coagulant, etc.) other than the acrylic polymer can be reduced.
[0106] The washing method is not particularly limited, and a method of washing with water by mixing the added water with the water-containing pellets can be cited. The temperature during washing with water is not particularly limited, but is preferably 5° C. to 60° C., more preferably 10° C. to 50° C. In addition, the mixing time is not particularly limited, but is preferably 1 minute to 60 minutes, more preferably 2 minutes to 30 minutes.
[0107] The amount of water added to the water-containing pellets during water washing is not particularly limited, but is preferably 150 parts by mass or more and 9800 parts by mass or less, and more preferably 150 parts by mass or more and 1800 parts by mass or less, relative to 100 parts by mass of the acrylic polymer contained in the water-containing pellets, from the viewpoint of being able to effectively reduce the content (residual amount) of the coagulant in the finally obtained adhesive composition.
[0108] As the number of times of washing, it is not particularly limited, and can be 1 time, from the viewpoint of reducing the content (residual amount) of the coagulant in the final binder composition, preferably more than 2 times and less than 10 times, more preferably more than 3 times and less than 8 times. In addition, although from the viewpoint of reducing the content (residual amount) of the coagulant in the final binder composition, the more the better the number of times of washing, even if the cleaning and the removal effect of the coagulant exceeding the above-mentioned scope are carried out, the number of operations can be increased on the other hand, causing the manufacturing efficiency to be significantly reduced. And then, in order to further reduce the content (residual amount) of the coagulant, it is necessary to dissolve it temporarily in an organic solvent such as toluene, and then put it into a completely different process such as a method of solidifying it in methanol. Therefore, it is preferably carried out with a coagulation water washing mode with good industrial manufacturing efficiency, and it is preferably made to wash the number of times in the above-mentioned scope.
[0109] In the cleaning step, after water cleaning, acid cleaning using an acid as a cleaning liquid may be further performed.
[0110] <<Drying process>>
[0111] In the drying step, the water-containing pellets that have been subjected to the above-mentioned washing step are dried to obtain a coagulated dry product containing an acrylic polymer and a coagulant.
[0112] The drying method that can be used in the drying step is not particularly limited, and for example, a screw extrusion dryer, a kneading dryer, an expansion dryer, a hot air dryer, a reduced pressure dryer, or the like can be used for drying. In addition, a drying method combining these can be used. Furthermore, before drying in the drying step, the water-containing pellets can be filtered using a sieve such as a rotary screen or a vibrating screen, or a centrifugal dehydrator, etc., as needed.
[0113] Here, the drying temperature in the drying step is not particularly limited and varies depending on the dryer used for drying. For example, when a hot air dryer is used, the drying temperature is preferably 80°C to 200°C, more preferably 100°C to 170°C.
[0114] <<Other Processes>>
[0115] There are no particular limitations on other steps that may be included in the method for producing the adhesive composition.
[0116] For example, the solidified dried product obtained in the above-mentioned drying step may be used as the binder composition directly, or a step of adding an organic solvent to the solidified dried product (organic solvent adding step) may be performed after the drying step to use a liquid composition containing an acrylic polymer, a coagulant and an organic solvent as the binder composition.
[0117] (Slurry composition for all-solid secondary battery)
[0118] The slurry composition of the present invention comprises a solid electrolyte and the above-mentioned binder composition containing an organic solvent. In other words, the slurry composition of the present invention is a composition in which at least the solid electrolyte, the above-mentioned acrylic polymer and the above-mentioned coagulant are dispersed and / or dissolved in an organic solvent.
[0119] Furthermore, since the slurry composition of the present invention is prepared using the above-mentioned binder composition of the present invention, the slurry composition can form a solid electrolyte-containing layer that enables the all-solid secondary battery to exhibit excellent high-temperature storage characteristics.
[0120] When the slurry composition for all-solid secondary batteries of the present invention is used to form an electrode composite material layer (ie, when it is a slurry composition for all-solid secondary battery electrodes), it usually contains at least a solid electrolyte, an acrylic polymer, a coagulant, and an organic solvent.
[0121] In addition, when the slurry composition for an all-solid secondary battery of the present invention is used to form a solid electrolyte layer (that is, when it is a slurry composition for an all-solid secondary battery solid electrolyte layer), it usually does not contain an electrode active material, and contains at least a solid electrolyte, an acrylic polymer, a coagulant and an organic solvent.
[0122] <Solid Electrolyte>
[0123] As the solid electrolyte, either an inorganic solid electrolyte or an organic solid electrolyte can be used, but an inorganic solid electrolyte is preferably used.
[0124] As an inorganic solid electrolyte, there is no particular limitation, and a crystalline inorganic ion conductor, an amorphous inorganic ion conductor or a mixture thereof can be used. Moreover, for example, in the case where the all-solid secondary battery is an all-solid lithium ion secondary battery, as an inorganic solid electrolyte, a crystalline inorganic lithium ion conductor, an amorphous inorganic lithium ion conductor or a mixture thereof can usually be used. Among them, from the viewpoint of improving battery performance such as high temperature storage characteristics, the inorganic solid electrolyte preferably includes a sulfide-based inorganic solid electrolyte.
[0125] In addition, as an example, the case where the slurry composition for all-solid secondary batteries is a slurry composition for all-solid lithium ion secondary batteries will be described below, but the present invention is not limited to the following example.
[0126] In addition, examples of crystalline inorganic lithium ion conductors include Li3N, LISICON (Li 14 Zn(GeO4)4), perovskite-type Li 0.5 La 0.5 TiO3, garnet-type Li7La3Zr2O 10 、LIPON(Li 3+y PO 4-x N x )、Thio-LISICON(Li 3.25 Ge 0.25 P 0.75 S4) etc.
[0127] The above-mentioned crystalline inorganic lithium ion conductors can be used alone or in combination of two or more.
[0128] In addition, as an amorphous inorganic lithium ion conductor, there is no particular limitation as long as it contains sulfur atoms and has ion conductivity, and examples include glass Li-Si-SO, Li-PS, and conductors formed using a raw material composition containing Li2S and a sulfide of an element from Group 13 to Group 15 of the periodic table.
[0129] Here, as the above-mentioned elements of Groups 13 to 15, for example, Al, Si, Ge, P, As, Sb, etc. can be cited. In addition, as sulfides of elements of Groups 13 to 15, specifically, Al2S3, SiS2, GeS2, P2S3, P2S5, As2S3, Sb2S3, etc. can be cited. Furthermore, as a method for synthesizing an amorphous inorganic lithium ion conductor using a raw material compound, for example, an amorphization method such as a mechanical grinding method and a melt quenching method can be cited. Moreover, as an amorphous inorganic lithium ion conductor formed using a raw material composition containing Li2S and a sulfide of an element of Groups 13 to 15 of the periodic table, Li2S-P2S5, Li2S-SiS2, Li2S-GeS2 or Li2S-Al2S3 is preferred, and Li2S-P2S5 is more preferred.
[0130] The above-mentioned amorphous inorganic lithium ion conductors can be used alone or in combination of two or more.
[0131] Among the above, as an inorganic solid electrolyte for all-solid lithium ion secondary batteries, from the viewpoint of improving battery performance such as high-temperature storage characteristics, an amorphous inorganic lithium ion conductor is preferred, and an amorphous sulfide containing Li and P is more preferred. Amorphous sulfides containing Li and P have high lithium ion conductivity, and thus can be used as an inorganic solid electrolyte to reduce the internal resistance of the battery and improve the output characteristics.
[0132] In addition, from the viewpoint of reducing the internal resistance of the battery and improving the output characteristics, the amorphous sulfide containing Li and P is more preferably a sulfide glass containing Li2S and P2S5, and is particularly preferably a sulfide glass produced from a mixed raw material of Li2S and P2S5 with a molar ratio of Li2S:P2S5 of 65:35 to 85:15. In addition, the amorphous sulfide containing Li and P is preferably a sulfide glass ceramic obtained by reacting a mixed raw material of Li2S and P2S5 with a molar ratio of Li2S:P2S5 of 65:35 to 85:15 by a mechanochemical method. In addition, from the viewpoint of maintaining the lithium ion conductivity at a high state, the mixed raw material preferably has a molar ratio of Li2S:P2S5 of 68:32 to 80:20.
[0133] In addition, the inorganic solid electrolyte may further include at least one sulfide selected from Al2S3, B2S3 and SiS2 as a starting material in addition to the above-mentioned Li2S and P2S5, to the extent that the ion conductivity is not reduced. When the sulfide is added, the glass component in the inorganic solid electrolyte can be stabilized.
[0134] Similarly, the inorganic solid electrolyte may contain at least one lithium orthooxoate selected from Li3PO4, Li4SiO4, Li4GeO4, Li3BO3 and Li3AlO3 in addition to Li2S and P2S5. When the lithium orthooxoate is contained, the glass component in the inorganic solid electrolyte can be stabilized.
[0135] <Acrylic polymer>
[0136] The acrylic polymer is contained in the binder composition, and specifically, the polymers exemplified in the above-mentioned section of “binder composition for all-solid secondary batteries” can be used.
[0137] In the slurry composition, the binder may be dissolved in the solvent, or may be dispersed in the form of particles without being dissolved in the solvent.
[0138] Here, the amount of acrylic acid polymer contained in the slurry composition for all-solid secondary batteries is not particularly limited, and relative to 100 parts by mass of solid electrolyte, it is preferably 0.05 parts by mass or more, more preferably 0.1 parts by mass or more, more preferably 0.2 parts by mass or more, preferably 5 parts by mass or less, more preferably 3 parts by mass or less, and more preferably 2 parts by mass or less. If the amount of acrylic acid polymer is above the lower limit, a solid electrolyte layer can be formed well. In addition, if the amount of acrylic acid polymer is below the upper limit, the reduction of ionic conductivity of the solid electrolyte layer can be suppressed.
[0139] <Coagulant>
[0140] The coagulant is contained in the binder composition, and specifically, the coagulants exemplified in the above-mentioned section of “binder composition for all-solid secondary batteries” can be used.
[0141] As described above, the coagulant is derived from the binder composition, and therefore the content of the coagulant relative to the acrylic polymer in the slurry composition of the present invention is the same as the content of the coagulant relative to the acrylic polymer in the binder composition of the present invention described above.
[0142] <Organic Solvents>
[0143] As the organic solvent, the organic solvents exemplified in the above-mentioned section of “binder composition for all-solid secondary batteries” can be used.
[0144] In addition, the organic solvent contained in the slurry composition may be only the organic solvent contained in the binder composition, or may be separately added when preparing the slurry composition.
[0145] <Electrode Active Material>
[0146] Here, the electrode active material is a material that transfers electrons in the electrode of the all-solid secondary battery. And, for example, when the all-solid secondary battery is an all-solid lithium ion secondary battery, a material that can absorb and release lithium is generally used as the electrode active material.
[0147] In addition, as an example, the case where the slurry composition for all-solid secondary batteries is a slurry composition for all-solid lithium ion secondary batteries will be described below, but the present invention is not limited to the following example.
[0148] Furthermore, the positive electrode active material for the all-solid lithium ion secondary battery is not particularly limited, and examples thereof include positive electrode active materials formed of inorganic compounds and positive electrode active materials formed of organic compounds. In addition, the positive electrode active material may be a mixture of an inorganic compound and an organic compound.
[0149] Examples of positive electrode active materials formed from inorganic compounds include transition metal oxides, composite oxides of lithium and transition metals (lithium-containing composite metal oxides), transition metal sulfides, and the like. As the above-mentioned transition metals, Fe, Co, Ni, Mn, and the like can be used. Specific examples of inorganic compounds used for positive electrode active materials include lithium-containing composite metal oxides such as LiCoO2 (lithium cobalt oxide), LiNiO2, LiMnO2, LiMn2O4, LiFePO4, and LiFeVO4; transition metal sulfides such as TiS2, TiS3, and amorphous MoS2; Cu2V2O3, amorphous V2O-P2O5, MoO3, V2O5, and V6O 13 Transition metal oxides, etc. These compounds may be compounds partially substituted with elements.
[0150] The above-mentioned positive electrode active materials composed of inorganic compounds can be used alone or in combination of two or more.
[0151] Examples of the positive electrode active material composed of an organic compound include polyaniline, polypyrrole, polyacene, disulfide compounds, polysulfide compounds, N-fluoropyridine, Salt, etc.
[0152] The above-mentioned positive electrode active materials composed of organic compounds can be used alone or in combination of two or more.
[0153] In addition, as negative electrode active materials for all-solid lithium ion secondary batteries, carbon allotropes such as graphene and coke can be cited. In addition, negative electrode active materials formed by carbon allotropes can be used in the form of a mixture or a coating with metals, metal salts, oxides, etc. In addition, as negative electrode active materials, oxides or sulfates of silicon, tin, zinc, manganese, iron, nickel, etc.; metallic lithium; lithium alloys such as Li-Al, Li-Bi-Cd, Li-Sn-Cd; lithium transition metal nitrides; organic silicon, etc. can be used.
[0154] The above-mentioned negative electrode active materials can be used alone or in combination of two or more.
[0155] <Optional Ingredients>
[0156] The slurry composition of the present invention may contain components other than the above-mentioned solid electrolyte, acrylic polymer, coagulant, organic solvent, and electrode active material.
[0157] As such arbitrary components, known binders, conductive materials, dispersants, leveling agents, defoamers, and reinforcing materials other than acrylic polymers can be cited. Furthermore, for example, when the all-solid secondary battery is a lithium ion secondary battery, lithium salts can also be cited as other components. These other components are not particularly limited as long as they do not affect the battery reaction.
[0158] As known binding agents except acrylic polymers, macromolecular compounds such as fluorine-based polymers, diene polymers, nitrile polymers can be used. These macromolecular compounds can be used alone or in combination. Here, as fluorine-based polymers, diene polymers and nitrile polymers, for example, fluorine-based polymers, diene polymers and nitrile polymers recorded in Japanese Patent Laid-Open No. 2012-243476 Gazette can be used.
[0159] Conductive materials are used to ensure the electrical contact between electrode active materials in the electrode composite material layer formed using a slurry composition for all-solid secondary batteries (slurry composition for all-solid secondary battery electrodes). Moreover, as conductive materials, it is possible to use: carbon black (e.g., acetylene black, Ketjen black (registered trademark), furnace carbon black, etc.), single-layer or multi-layer carbon nanotubes (multi-layer carbon nanotubes include stacked cups), carbon nanohorns, vapor-grown carbon fibers, ground carbon fibers obtained by sintering and crushing polymer fibers, single-layer or multi-layer graphene, sintering non-woven fabrics containing polymer fibers, and other conductive carbon materials such as carbon non-woven fabric sheets; various metal fibers or foils, etc.
[0160] These can be used alone or in combination of two or more.
[0161] The lithium salt, dispersant, leveling agent, defoaming agent, reinforcing material, and the like are not particularly limited, and for example, those described in Japanese Patent Application Laid-Open No. 2012-243476 can be used.
[0162] <Method for producing slurry composition>
[0163] Moreover, the method for manufacturing the above-mentioned slurry composition of the present invention is not particularly limited, and the slurry composition can be obtained by mixing the binder composition prepared according to the steps described in the "Method for manufacturing the binder composition", the solid electrolyte, and the electrode active material and arbitrary components added as needed in the presence of an organic solvent.
[0164] (with solid electrolyte layer)
[0165] The solid electrolyte layer of the present invention is a layer containing a solid electrolyte. Examples of the solid electrolyte layer include an electrode composite material layer (positive electrode composite material layer, negative electrode composite material layer) that transfers electrons via an electrochemical reaction, and a solid electrolyte layer disposed between a positive electrode composite material layer and a negative electrode composite material layer that are opposite to each other.
[0166] Moreover, the solid electrolyte layer of the present invention is formed using the above-mentioned slurry composition for all-solid secondary batteries, and can be formed by, for example, applying the above-mentioned slurry composition on a suitable substrate surface to form a coating film, and then drying the formed coating film. That is, the solid electrolyte layer of the present invention is formed by the dried product of the above-mentioned slurry composition, usually comprising at least a solid electrolyte, an acrylic polymer and a coagulant. In addition, the components contained in the solid electrolyte layer are the components contained in the above-mentioned slurry composition, and the content ratio of these components is usually equal to the content ratio in the above-mentioned slurry composition.
[0167] Furthermore, since the solid electrolyte-containing layer of the present invention is formed from the slurry composition for an all-solid secondary battery of the present invention, the all-solid secondary battery can exhibit excellent high-temperature storage characteristics.
[0168] <Base Material>
[0169] Here, the substrate to which the slurry composition is applied is not limited. For example, a coating film of the slurry composition can be formed on the surface of a release substrate, the coating film is dried to form a solid electrolyte layer, and the release substrate is peeled off from the solid electrolyte layer. The solid electrolyte layer peeled off from the release substrate can be used as a self-supporting film to form a battery component (e.g., an electrode, a solid electrolyte layer, etc.) of an all-solid secondary battery.
[0170] However, from the viewpoint of omitting the process of stripping the solid electrolyte layer and improving the manufacturing efficiency of the battery component, it is preferred to use a current collector or an electrode as a substrate. Specifically, when preparing the electrode composite material layer, the slurry composition is preferably applied to the current collector as a substrate. In addition, when preparing the solid electrolyte layer, the slurry composition is preferably applied to the electrode (positive electrode or negative electrode).
[0171] <<Current collector>>
[0172] As the current collector, a material having conductivity and electrochemical durability can be used. Specifically, as the current collector, a current collector formed of, for example, iron, copper, aluminum, nickel, stainless steel, titanium, tantalum, gold, platinum, etc. can be used. Among them, as the current collector for the negative electrode, copper foil is particularly preferred. In addition, as the current collector for the positive electrode, aluminum foil is particularly preferred. In addition, the above materials can be used alone or in combination of two or more in any ratio.
[0173] <<Electrode>>
[0174] The electrodes (positive electrode and negative electrode) are not particularly limited, and examples thereof include electrodes in which an electrode composite material layer including an electrode active material, a solid electrolyte, and a binder is formed on the above-mentioned current collector.
[0175] The electrode active material, solid electrolyte and binder included in the electrode composite material layer in the electrode are not particularly limited, and known electrode active materials, solid electrolytes and binders can be used. In addition, the electrode composite material layer in the electrode can also be an electrode composite material layer containing a solid electrolyte layer belonging to the present invention.
[0176] <Method for Forming Solid Electrolyte-Containing Layer>
[0177] As a method for forming a solid electrolyte-containing layer on the above-mentioned substrate such as a current collector or an electrode, the following method can be mentioned.
[0178] 1) A method of applying the slurry composition of the present invention on the surface of a substrate (the surface on the electrode composite material layer side in the case of an electrode, the same below), and then drying;
[0179] 2) A method of dipping a substrate in the slurry composition of the present invention and then drying the substrate; and
[0180] 3) A method in which the slurry composition of the present invention is applied to a release substrate, dried to produce a solid electrolyte-containing layer, and the obtained solid electrolyte-containing layer is transferred to the surface of an electrode or the like.
[0181] Among these, the method 1) is particularly preferred because it is easy to control the thickness of the solid electrolyte layer. Specifically, the method 1) includes a step of applying the slurry composition on a substrate (coating step), and a step of drying the slurry composition applied on the substrate to form a solid electrolyte layer (solid electrolyte layer forming step).
[0182] <<Coating process>>
[0183] In the coating step, the method for coating the slurry composition on the substrate is not particularly limited, and examples thereof include doctor blade coating, reverse roll coating, direct roll coating, gravure printing, extrusion, and brush coating.
[0184] <<Solid Electrolyte-Containing Layer Forming Step>>
[0185] In addition, in the step of forming the solid electrolyte layer, the method for drying the slurry composition on the substrate is not particularly limited, and a known method can be used. Examples of the drying method include: a drying method using warm air, hot air, or low-humidity air; a vacuum drying method; and a drying method using irradiation of infrared rays, electron beams, or the like.
[0186] When the solid electrolyte-containing layer is an electrode composite material layer, it is preferably subjected to a pressing treatment after drying using a roll press machine, etc. By performing a pressing treatment, the obtained electrode composite material layer can be further densified.
[0187] (electrode)
[0188] Moreover, the electrode formed by forming an electrode composite material layer on a current collector using the slurry composition for an all-solid secondary battery of the present invention has an electrode composite material layer comprising at least a solid electrolyte, an acrylic polymer, a coagulant and an electrode active material, which can enable the all-solid secondary battery to exhibit excellent high-temperature storage characteristics.
[0189] (Solid electrolyte layer)
[0190] Furthermore, the solid electrolyte layer formed using the slurry composition for an all-solid secondary battery of the present invention contains at least a solid electrolyte, an acrylic polymer, and a coagulant, and can enable the all-solid secondary battery to exhibit excellent high-temperature storage characteristics.
[0191] (All-solid-state secondary battery)
[0192] The all-solid secondary battery of the present invention is characterized in that it usually has a positive electrode, a solid electrolyte layer and a negative electrode, and at least one of the positive electrode composite material layer of the positive electrode, the negative electrode composite material layer of the negative electrode and the solid electrolyte layer is a solid electrolyte layer of the present invention. That is, the all-solid secondary battery of the present invention has: a positive electrode having a positive electrode composite material layer formed using a slurry composition for a positive electrode of an all-solid secondary battery as a slurry composition for an all-solid secondary battery of the present invention, a negative electrode having a negative electrode composite material layer formed using a slurry composition for a negative electrode of an all-solid secondary battery as a slurry composition for an all-solid secondary battery of the present invention, and at least one of the solid electrolyte layers formed using a slurry composition for a solid electrolyte layer of an all-solid secondary battery as a slurry composition for an all-solid secondary battery of the present invention.
[0193] Furthermore, the all-solid secondary battery of the present invention has the solid electrolyte-containing layer of the present invention and therefore has excellent battery performance such as high-temperature storage characteristics.
[0194] Here, as an electrode for an all-solid secondary battery that can be used in the all-solid secondary battery of the present invention and has an electrode composite material layer containing a solid electrolyte layer that does not belong to the present invention, there is no particular limitation as long as it has an electrode composite material layer containing a solid electrolyte layer that does not belong to the present invention, and any electrode for an all-solid secondary battery can be used.
[0195] In addition, the solid electrolyte layer that does not belong to the solid electrolyte layer of the present invention and can be used for the all-solid secondary battery of the present invention is not particularly limited, and any solid electrolyte layer such as the solid electrolyte layer described in Japanese Patent Gazette No. 2012-243476, Japanese Patent Gazette No. 2013-143299 and Japanese Patent Gazette No. 2016-143614 can be used.
[0196] Moreover, the all-solid secondary battery of the present invention can be obtained in the following manner: the positive electrode and the negative electrode are stacked in a manner that the positive electrode composite material layer of the positive electrode and the composite material layer of the negative electrode are relative to each other via a solid electrolyte layer, and after arbitrarily pressurizing to obtain a laminate, according to the shape of the battery, it is placed in a battery container in the original state or by winding, folding, etc., and sealed. In addition, porous metal mesh, fuse, PTC element and other overcurrent protection elements, guide plates, etc. can be placed in the battery container as needed to prevent the pressure inside the battery from rising and overcharging and discharging. The shape of the battery can be any of coin type, button type, sheet type, cylindrical type, square, flat type, etc.
[0197] Example
[0198] Hereinafter, the present invention will be specifically described based on Examples, but the present invention is not limited to these Examples. In the following description, "%" and "part" indicating an amount are based on mass unless otherwise specified.
[0199] In the examples and comparative examples, the content of the coagulant in the binder composition, the recovery rate of the acrylic polymer, and the high-temperature storage characteristics of the all-solid secondary battery were measured and evaluated by the following methods.
[0200] <Content of coagulant>
[0201] The binder composition (solidified dried product) is subjected to elemental analysis using inductively coupled plasma atomic emission spectrometry (ICP-AES), thereby determining the content of the coagulant in the solidified dried product. Specifically, the content ratio of the elements constituting the coagulant used in the binder composition is determined by elemental analysis, and the content of the coagulant is determined based on the determined content ratio.
[0202] <Recovery Rate of Acrylic Acid-Based Polymer>
[0203] The ratio of the amount of the acrylic polymer that can be recovered as the adhesive composition to the assumed theoretical yield obtained from the total amount of monomers fed and the polymerization conversion rate was calculated and taken as the recovery rate (%).
[0204] <High temperature storage characteristics>
[0205] The capacity of the fabricated all-solid secondary battery was measured and taken as the initial capacity C0. After the initial capacity was measured, the all-solid secondary battery was stored in a thermostatic chamber at 80°C for 100 hours, 500 hours, and 1000 hours, and the capacity C0 after storage for 100 hours was measured. 100 、Capacity C after 500 hours of storage 500 、Capacity C after 1000 hours of storage 1000 Then, the capacity retention rate (C 100 / C0×100%、C 500 / C0×100%、C 1000 / C0×100%). The higher the capacity retention rate is, the better the high-temperature storage characteristics of the all-solid secondary battery are.
[0206] In addition, the capacity of the all-solid secondary battery was measured as follows.
[0207] The all-solid secondary battery was charged and discharged as follows: the battery was charged to 4.2 V at a constant current and constant voltage at 0.1 C at 25° C., then charged at a constant voltage, and then discharged to 3.0 V at a constant current of 0.1 C. Five charge and discharge cycles were performed, and the discharge capacity at the fifth cycle was taken as the capacity.
[0208] (Example 1)
[0209] <Preparation of Adhesive Composition>
[0210] <<Emulsion polymerization process>>
[0211] Into a mixing container equipped with a homogenizer were added 47.701 parts of pure water, 49.3 parts of ethyl acrylate and 49.3 parts of n-butyl acrylate as (meth)acrylate monomers (the ratio of ethyl acrylate to n-butyl acrylate in the total monomers was 50% 50%), 0.709 parts of sodium lauryl sulfate (trade name "EMAL 2FG", manufactured by Kao Corporation) as an anionic surfactant, and 1.82 parts of polyoxyethylene lauryl ether (trade name "EMULGEN 105", manufactured by Kao Corporation) as a nonionic surfactant, and the mixture was stirred to obtain a monomer emulsion.
[0212] Next, 170.853 parts of pure water and 2.98 parts of the monomer emulsion obtained above were added to a polymerization reaction tank equipped with a thermometer and a stirring device, and cooled to a temperature of 12°C under a nitrogen stream. Next, 145.85 parts of the monomer emulsion obtained above, 0.00033 parts of ferrous sulfate and 0.264 parts of sodium ascorbate as a reducing agent, and 7.72 parts (0.22 parts in terms of potassium persulfate) of a 2.85% potassium persulfate aqueous solution as a polymerization initiator were continuously added dropwise to the polymerization reaction tank over a period of 3 hours. Then, the reaction was continued for 1 hour while the temperature in the polymerization reaction tank was maintained at 23°C. After confirming that the polymerization conversion rate reached 95%, hydroquinone was added as a polymerization terminator to terminate the polymerization reaction, thereby obtaining an emulsion polymerization liquid.
[0213] <<Solidification process>>
[0214] The emulsion polymerized liquid obtained by the emulsion polymerization step was transferred to a coagulation tank, and 60 parts of industrial water were added to 100 parts of the emulsion polymerized liquid to prepare a mixed liquid. After the mixed liquid was heated to 85° C., 3.3 parts (11 parts relative to 100 parts of the acrylic acid polymer contained in the mixed liquid) of sodium sulfate as a coagulant were continuously added while stirring at 85° C. to coagulate the acrylic acid polymer, thereby obtaining aqueous granules of the acrylic acid polymer.
[0215] <<Cleaning process>>
[0216] 160 parts of industrial water were added to 100 parts of the solid content of the water-containing pellets obtained in the washing step, and the pellets were stirred in a coagulation tank at 15° C. for 5 minutes, and then the water was drained from the coagulation tank to wash the water-containing pellets. This washing was repeated 4 times in total.
[0217] <<Drying process>>
[0218] The water-containing granules washed with water in the cleaning process were dried at 110°C for 1 hour in a hot air dryer to obtain a solidified dry product. The solidified dry product (binder composition) was used to measure the content of the coagulant and the recovery rate of the acrylic polymer. The results are shown in Table 1. In addition, by NMR measurement, it was confirmed that the acrylic polymer contained 50% of ethyl acrylate units and 50% of n-butyl acrylate units. In addition, in other embodiments and comparative examples, it was also confirmed that the proportion of each monomer in the total monomers used to prepare the acrylic polymer was consistent with the proportion of the monomer unit from the monomer in the acrylic polymer.
[0219] <<Organic solvent adding process>>
[0220] The solidified dried product obtained in the drying step was dissolved in xylene, and then heated and decompressed using an evaporator to prepare a liquid composition (water content: 82 mass ppm, solid content concentration: 7%) as a binder composition.
[0221] <Preparation of Slurry Composition for Solid Electrolyte Layer>
[0222] In a glove box under an argon atmosphere (water concentration 0.6 mass ppm, oxygen concentration 1.8 mass ppm), 100 parts of sulfide glass formed of Li2S and P2S5 (Li2S / P2S5=70 mol% / 30 mol%, number average particle size: 1.2 μm, cumulative 90% particle size: 2.1 μm) as a solid electrolyte and 2 parts (in terms of solid content equivalent) of the above-obtained binder composition were mixed, and xylene as an organic solvent was further added to adjust the solid content concentration to 65 mass %. Then, the mixture was mixed by a planetary mixer to prepare a slurry composition for a solid electrolyte layer.
[0223] <Preparation of positive electrode slurry composition>
[0224] 100 parts of lithium cobalt oxide (average particle size: 11.5 μm) as a positive electrode active material, 150 parts of sulfide glass formed by Li2S and P2S5 (Li2S / P2S5=70 mol% / 30 mol%, number average particle size: 0.4 μm) as a solid electrolyte, 13 parts of acetylene black as a conductive agent, and 2 parts (in terms of solid content equivalent) of the above-obtained binder composition were mixed, and xylene as an organic solvent was further added to adjust the solid content concentration to 78%, and then mixed for 60 minutes by a planetary mixer. Then, the solid content concentration was further adjusted to 74% with xylene and mixed for 10 minutes to prepare a positive electrode slurry composition.
[0225] <Preparation of Negative Electrode Slurry Composition>
[0226] 100 parts of graphite (average particle size: 20 μm) as a negative electrode active material, 50 parts of sulfide glass formed by Li2S and P2S5 (Li2S / P2S5=70 mol% / 30 mol%, number average particle size: 0.4 μm) as a solid electrolyte, and 2 parts (equivalent amount of solid content) of the above-obtained binder composition were mixed, and xylene as an organic solvent was further added. After adjusting the solid content concentration to 60%, the mixture was mixed by a planetary mixer to prepare a slurry composition for a negative electrode.
[0227] <Manufacturing of all-solid-state secondary batteries>
[0228] The positive electrode slurry composition was applied on the surface of a current collector (aluminum foil, thickness: 20 μm) and dried (110° C., 20 minutes) to form a positive electrode composite material layer with a thickness of 50 μm, thereby obtaining a positive electrode. In addition, the negative electrode slurry composition was applied on the surface of another current collector (copper foil, thickness: 18 μm) and dried (110° C., 20 minutes) to form a negative electrode composite material layer with a thickness of 30 μm, thereby obtaining a negative electrode.
[0229] Next, the solid electrolyte layer slurry composition was applied onto the surface of the positive electrode composite material layer of the positive electrode and dried (110° C., 10 minutes) to form a solid electrolyte layer with a thickness of 18 μm, thereby obtaining a positive electrode with a solid electrolyte layer.
[0230] The above-mentioned positive electrode with a solid electrolyte layer and the negative electrode are laminated in a manner that the solid electrolyte layer of the positive electrode with a solid electrolyte layer contacts the negative electrode composite material layer of the negative electrode, and pressed to obtain an all-solid secondary battery. The thickness of the solid electrolyte layer of the pressed all-solid secondary battery is 11 μm. The high-temperature storage characteristics of the all-solid secondary battery are evaluated. The results are shown in Table 1.
[0231] (Example 2)
[0232] When preparing the binder composition, in the emulsion polymerization process, 2-ethylhexyl acrylate was further used as a monomer (the ratio of ethyl acrylate 48%, n-butyl acrylate 45%, and 2-ethylhexyl acrylate 7% in the total monomers), magnesium sulfate was used instead of sodium sulfate as a coagulant in the coagulation process, and the amount of industrial water added in the cleaning process was changed to 150 parts. In addition, the same method as Example 1 was carried out to manufacture a binder composition (water content: 75 mass ppm, solid content concentration: 7.5%), various slurry compositions, and all-solid secondary batteries, and the results were measured and evaluated. The results are shown in Table 1.
[0233] (Example 3)
[0234] When preparing the binder composition, the number of water washing in the washing process was changed to 1 time. In the same manner as in Example 1, a binder composition (water content: 58 mass ppm, solid content concentration: 7.5%), various slurry compositions, and all-solid secondary batteries were manufactured, and measured and evaluated. The results are shown in Table 1.
[0235] (Example 4)
[0236] When preparing the binder composition, in the emulsion polymerization process, the amount of ethyl acrylate and n-butyl acrylate used as monomers was changed to 55% and 45% respectively in the total monomers, in the coagulation process, the amount of sodium sulfate as a coagulant was changed to 1.2 parts, and in the cleaning process, the amount of industrial water added was changed to 200 parts. In the same manner as in Example 1, a binder composition (water content: 88 mass ppm, solid content concentration: 7.2%), various slurry compositions, and all-solid secondary batteries were manufactured, and measured and evaluated. The results are shown in Table 1.
[0237] (Example 5)
[0238] In the preparation of the binder composition, the slurry composition for the solid electrolyte layer, the slurry composition for the positive electrode, and the slurry composition for the negative electrode, diisobutyl ketone was used instead of xylene. In the same manner as in Example 1, a binder composition (water content: 95 mass ppm, solid content concentration: 8.2%), various slurry compositions, and all-solid secondary batteries were manufactured, and measured and evaluated. The results are shown in Table 2.
[0239] (Example 6)
[0240] In the preparation of the binder composition, the slurry composition for the solid electrolyte layer, the slurry composition for the positive electrode, and the slurry composition for the negative electrode, n-butyl ether was used instead of xylene. In the same manner as in Example 1, a binder composition (water content: 48 mass ppm, solid content concentration: 7.5%), various slurry compositions, and all-solid secondary batteries were manufactured, and measured and evaluated. The results are shown in Table 2.
[0241] (Comparative Example 1)
[0242] When preparing the binder composition, in the solidification process, the amount of sodium sulfate as a coagulant was changed to 15 parts. In the same manner as in Example 1, a binder composition (water content: 68 mass ppm, solid content concentration: 7.4%), various slurry compositions, and all-solid secondary batteries were manufactured, and measured and evaluated. The results are shown in Table 2.
[0243] (Comparative Example 2)
[0244] In the preparation of the binder composition, the washing step was not performed, and the water-containing granules obtained by the coagulation step were directly supplied to the drying step. In the same manner as in Example 1, a binder composition (water content: 58 mass ppm, solid content concentration: 7.5%), various slurry compositions, and all-solid secondary batteries were manufactured, and measured and evaluated. The results are shown in Table 2.
[0245] (Comparative Example 3)
[0246] When preparing the binder composition, the amount of sodium sulfate as a coagulant was changed to 0.1 parts in the coagulation step. The same procedure as in Example 1 was followed, and although a binder composition (water content: 86 mass ppm, solid content concentration: 7.6%) was prepared, the coagulation was insufficient due to insufficient amount of the coagulant, resulting in an extremely low recovery rate of the acrylic polymer (45%), and various slurry compositions and all-solid secondary batteries were not manufactured.
[0247] In addition, in Table 1 and Table 2 shown below,
[0248] "XY" stands for xylene,
[0249] "DIK" stands for diisobutyl ketone,
[0250] "BE" stands for n-butyl ether.
[0251] [Table 1]
[0252]
[0253] [Table 2]
[0254]
[0255] Tables 1 and 2 show that in Examples 1 to 6, in which a binder composition containing an acrylic polymer and a coagulant with a coagulant content within a predetermined range was used to prepare the solid electrolyte layer, all-solid secondary batteries with excellent high-temperature storage characteristics were obtained.
[0256] On the other hand, as shown in Table 2, in Comparative Examples 1 and 2 in which a binder composition containing a coagulant exceeding the prescribed upper limit was used to prepare the solid electrolyte-containing layer, the high-temperature storage characteristics of the all-solid secondary battery were impaired.
[0257] Furthermore, as can be seen from Table 2, in Comparative Example 3 in which the amount of the coagulant used was reduced to make the content of the coagulant contained in the adhesive composition less than the prescribed lower limit when preparing the adhesive composition, the recovery rate of the acrylic polymer was significantly reduced as described above.
[0258] Industrial Applicability
[0259] According to the present invention, it is possible to provide a binder composition for an all-solid secondary battery and a slurry composition for an all-solid secondary battery that can form a solid electrolyte-containing layer that enables an all-solid secondary battery to exhibit excellent high-temperature storage characteristics.
[0260] Furthermore, according to the present invention, it is possible to provide a solid electrolyte layer containing an all-solid secondary battery that enables the all-solid secondary battery to exhibit excellent high-temperature storage characteristics and an all-solid secondary battery having excellent high-temperature storage characteristics.
Claims
1. A binder composition for an all-solid secondary battery, comprising an acrylic polymer, a coagulant in an amount of 500 ppm by mass or more and 5000 ppm by mass or less relative to the acrylic polymer, and an organic solvent, The coagulant is a metal sulfate having a valency of 1 or more and 3 or less.
2. The binder composition for an all-solid secondary battery according to claim 1, wherein The acrylic polymer is an emulsion polymer. 3 . A slurry composition for an all-solid secondary battery, comprising a solid electrolyte and the binder composition for an all-solid secondary battery according to claim 2 .
4. The slurry composition for all-solid secondary batteries according to claim 3, wherein The solid electrolyte is an inorganic solid electrolyte. 5 . The slurry composition for an all-solid secondary battery according to claim 3 , further comprising an electrode active material. 6 . A solid electrolyte-containing layer formed using the slurry composition for an all-solid secondary battery according to claim 3 . 7 . An all-solid secondary battery comprising the solid electrolyte-containing layer according to claim 6 .
Citation Information
Patent Citations
Method for manufacturing all-solid secondary battery
JP2012243476A
Electrode material, electrode and battery using the same
JP2013143299A
All-solid battery
JP2016143614A
All-solid secondary battery
WO2016152262A1
All-solid secondary battery
JP2016181471A